Enhanced dielectric and piezoelectric properties of Fe-doped ZnO/PVDF-TrFE composite films. (October 2020) - Sahoo, Rajesh; Mishra, Suvrajyoti; Unnikrishnan, Lakshmi; Mohanty, Smita; Mahapatra, Swapna; Nayak, Sanjay Kumar; Anwar, Shahid; Ramadoss, Ananthakumar
Abstract: Free-standing flexible Fe-doped ZnO (Z (1-x) F(x) O)/PVDF-TrFE nanocomposite films were prepared via solvent casting method with a constant filler/polymer ratio. The influence of Fe concentration (x = 0.01, 0.03 and 0.05) made no significant change in the crystalline β-phase of the composite films as confirmed from XRD, FTIR and DSC studies. Maximum enhancement in the dielectric and ferroelectric behaviour was observed for the composite films with x = 0.05 showing a dielectric permittivity of 21.03 at 1 kHz and a remnant polarization of 0.125 μC/cm 2 . These enhanced properties were attributed to the reduced crystal size of the nanoparticles, which affects the interface space polarization and the effective volume of composite films. Finally, the demonstration of enhanced piezoelectric properties of the composite film (x = 0.05) with 7 V output voltage under continuous finger tapping and driving LEDs makes it a potential device for energy harvesting applications. Graphical abstract: Image 1 Highlights: Composite films (Z(1-x) F(x) O/PVDF-TrFE) prepared via solvent casting method with constant filler/polymer ratio. Undisturbed crystalline β-phase achieved for different Fe concentrations (x = 0.01, 0.03 and 0.05). Films with x = 0.05 showed enhanced dielectric and ferroelectric properties. Z(1-x) F(x) O/PVDF-TrFE composite films exhibited a maximum voltage of 7 V (x = 0.05).